Monogenic Causes of Proteinuria in Children - Cil, Onur; Perwad, Farzana (Frontiers in Medicine, 2018)
Glomerular disease is a common cause for proteinuria and chronic kidney disease leading to end stage renal disease requiring dialysis or kidney transplantation in children. Nephrotic syndrome in children is diagnosed by the presence of a triad of proteinuria, hypoalbuminemia and edema. Minimal change disease is the most common histopathologic finding in children and adolescents with nephrotic syndrome. Focal segmental sclerosis is also found in children and is the most common pathologic finding in patients with monogenic causes of nephrotic syndrome. Current classification system for nephrotic syndrome is based upon response to steroid therapy as a majority of patients develop steroid sensitive nephrotic syndrome regardless of histopathologic diagnosis or the presence of genetic mutations. Recent studies investigating the genetics of nephrotic syndrome have shed light on the pathophysiology and mechanisms of proteinuria in nephrotic syndrome. Gene mutations have been identified in several subcellular compartments of the glomerular podocyte and play a critical role in mitochondrial function, actin cytoskeleton dynamics, cell-matrix interactions, slit diaphragm and podocyte integrity. A subset of genetic mutations are known to cause nephrotic syndrome that is responsive to immunosuppressive therapy but clinical data is limited with respect to renal prognosis and disease progression in a majority of patients. To date, more than fifty genes have been identified as causative factors in nephrotic syndrome in children and adults. As genetic testing becomes more prevalent and affordable, we expect rapid advances in our understanding of mechanisms of proteinuria and genetic diagnosis will help direct future therapy for individual patients.